2005
DOI: 10.1002/ajmg.a.30952
|View full text |Cite
|
Sign up to set email alerts
|

Cosegregation of the G7444A mutation in the mitochondrial COI/tRNASer(UCN) genes with the 12S rRNA A1555G mutation in a Chinese family with aminoglycoside‐induced and nonsyndromic hearing loss

Abstract: We report here on the characterization of a three-generation Chinese family with aminoglycosideinduced and nonsyndromic hearing impairment. Ten of 17 matrilineal relatives exhibited bilateral and sensorineural hearing impairment. Of these, nine matrilineal relatives, who had a history of exposure to aminoglycosides, exhibited variable severity and audiometric configuration of hearing loss. The dose and age at the time of drug administration seemed to be correlated with the severity of the hearing loss experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
1
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 42 publications
(55 reference statements)
5
93
1
1
Order By: Relevance
“…This mutation was implicated to be associated with nonsyndromic SNHL [55] or to influence the phenotypic expression of hearing loss associated with the A1555G mutation [56]. The pathogenicity was supported by a recent observation of two Chinese families with aminoglycosideinduced and nonsyndromic SNHL, in which the homoplasmic G7444A mutation was present only in the maternal lineage but not in other members of these pedigrees and 164 Chinese controls [57].…”
Section: Mitochondrial Trna Mutations Associated With Nonsyndromic Hementioning
confidence: 85%
See 2 more Smart Citations
“…This mutation was implicated to be associated with nonsyndromic SNHL [55] or to influence the phenotypic expression of hearing loss associated with the A1555G mutation [56]. The pathogenicity was supported by a recent observation of two Chinese families with aminoglycosideinduced and nonsyndromic SNHL, in which the homoplasmic G7444A mutation was present only in the maternal lineage but not in other members of these pedigrees and 164 Chinese controls [57].…”
Section: Mitochondrial Trna Mutations Associated With Nonsyndromic Hementioning
confidence: 85%
“…In the mitochondrial tRNA Ser(UCN) gene, five nonsyndromic deafness-associated mutations, A7445G [42][43][44], 7472insC [45][46][47], T7510C [48,84], T7511C [49][50][51][52][53], and G7444A [55][56][57], have been found in families from various ethnic backgrounds. These mutations often occur in homoplasmy or in high levels of heteroplasmy, indicating a high threshold for pathogenicity.…”
Section: Mitochondrial Trna Mutations Associated With Nonsyndromic Hementioning
confidence: 99%
See 1 more Smart Citation
“…Several families have been reported to have one mtDNA deafness-causing mutation and several other mtDNA variants described as polymorphisms, but only a few individuals were found with more than one mtDNA deafness-causing mutation. 16,19,22 THE GJB2 35delG AND A1555G mtDNA MUTATIONS IN A SPANISH FAMILY Ló pez-Bigas et al 17 studied the GJB2 35delG mutation in 154 deaf individuals with the A1555G mutation and also analyzed the entire coding region of GJB2 in 42 unrelated patients from their cohort. They detected only one family with the 35delG mutation in heterozygosity, including four patients also having the A1555G mutation and two patients with the A1555G alone.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that mutation m.1494C>T might associate with aminoglycoside-induced hearing loss in a large Chinese family [8,10,11]., while the mutation m.1555A>G may contribute to both aminoglycoside-induced and nonsyndromic hearing loss in families worldwide [12,13]. Both m.1555A>G and m.1494C>T mutations locate in a highly conserved region of 12SrRNA that is implicated in aminoglycoside binding in bacteria.…”
mentioning
confidence: 99%